2004
DOI: 10.1111/j.1346-8138.2004.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Leprosy Reactions in a Tertiary Hospital in Delhi

Abstract: A retrospective study of 531 leprosy patients was undertaken to study the profile of reactions in the post Multi-Drug-Therapy period in a tertiary hospital in Delhi. BT was the most common group. The prevalence of reactions was found to be 8.09% for the Type 1 and 4.70% for the Type 2 reactions for a male:female ratio of 2.2. The Type 1 reaction was most frequently observed in the BB group followed by BL, BT and LL groups respectively. More than half of the patients had reactions at the time of presentation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 5 publications
(9 reference statements)
10
41
0
Order By: Relevance
“…Moreover, geographic and ethnic variation among the proportions of leprosy subtypes also contributes to significant heterogeneity in reported prevalences, because T1Rs occur predominantly in patients with borderline leprosy. Consistent with observations in previous studies [10][11][12], the T1R prevalence was highest among patients with the BB and BL types of leprosy in this sample of Vietnamese case patients with leprosy (prevalence of 49% and 43%, respectively). Importantly, multivariate analysis revealed that borderline forms of leprosy are independent risk factors for T1Rs, as is a positive BI at leprosy diagnosis.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Moreover, geographic and ethnic variation among the proportions of leprosy subtypes also contributes to significant heterogeneity in reported prevalences, because T1Rs occur predominantly in patients with borderline leprosy. Consistent with observations in previous studies [10][11][12], the T1R prevalence was highest among patients with the BB and BL types of leprosy in this sample of Vietnamese case patients with leprosy (prevalence of 49% and 43%, respectively). Importantly, multivariate analysis revealed that borderline forms of leprosy are independent risk factors for T1Rs, as is a positive BI at leprosy diagnosis.…”
Section: Discussionsupporting
confidence: 94%
“…Importantly, multivariate analysis revealed that borderline forms of leprosy are independent risk factors for T1Rs, as is a positive BI at leprosy diagnosis. Finally, the number of skin lesions at diagnosis was also an independent risk factor for T1R in our sample, which is consistent with the documented impact of the extent of clinical disease on the risk of a T1R [9][10][11][12].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, one systematic review of ENL cases noted that the incidence of ENL is at least twice as high during MDT than at the time of the initial diagnosis, with the highest incidence in the first year of MDT 15. One study16 has noted leprosy reactions with concurrent TB infection; however, precipitating factors could not be elicited.…”
Section: Discussionmentioning
confidence: 99%